RESEARCH TRENDS & GAPS ASSESSMENT - WASTEWATER TREATMENT WITH COAGULATION AND FLOCCULATION METHODS - Artha Dewi Novitasari; Sudarno Sudarno; Nurandani Hardiyanti; Bimastyaji Surya Ramadan (RADJA PUBLIKA, 2025)
Industrial activities can cause negative impacts, one of which is the result of the production process which can cause pollution and environmental damage if the company does not process B3 waste in accordance with applicable regulations. With increasing concern for the environment, many companies or other interested parties are required to process liquid waste. Therefore, this study aims to find out from several existing research journals about the effectiveness of wastewater treatment methods and processes Poly Aluminum Chloride (PAC) and Aluminum Sulfate (Alum). The analysis method uses several software to find out the results of research analysis from several existing scientific literature. By using blibiometric analysis, it was found that research on wastewater treatment mostly uses coagulation and flocculation methods which have developed every year. To improve the results of wastewater treatment, it is necessary to consider several influencing factors such as dose, speed and duration of stirring during the experiment. From the results of several previous studies, it was found that the use of Poly Aluminum Chloride (PAC) was the most effective compared to Aluminum Sulfate (Alum) by comparing the decrease in the results of testing the specified quality standard parameters (for example pH,COD, BOD, turbidity, TSS, etc)